Standardized structural magnetic resonance imaging in multicentre studies using quantitative T1 and T2 imaging at 1.5 T. - Deoni, S; Williams, S; Jezzard, P; Suckling, J; Murphy, D; Jones, D (2008)
The ability to acquire MRI data with consistent tissue contrast at multiple time points, and/or across different imaging centres has become increasingly important as the number of large longitudinal and multicentre studies has grown. Here, the use of quantitative magnetic resonance relaxation times measurement, or, voxel-wise determination of the intrinsic longitudinal and transverse relaxation times, T1 and T2 respectively, for standardizing the structural imaging component of such studies is reported. To demonstrate the ability to standardize across multiple time-points and imaging centres, T1 and T2 maps of seven healthy volunteers were acquired using the rapid DESPOT1 and DESPOT2 (driven equilibrium single pulse observation of T1 and T2) mapping techniques at three centres across the United Kingdom (each centre utilizing scanners from competing manufacturers and/or with varying gradient performance). An average coefficient of variation of the estimates of T1 and T2 was found to be approximately 6.5% and 8%, respectively, across the three centres and comparable to that achieved between repeated imaging sessions performed at the same centre. With a total combined imaging time of less than 12 min for whole-brain approximately 1.2 mm isotropic voxel T1 and T2 maps, quantitative voxel-wise T1 and T2 mapping represents an attractive and easy-to-implement approach for signal intensity standardization and normalization. Further, as T1 and T2 are related to tissue microstructure and biochemistry, quantitative images provide additional diagnostic information that can be compared between patient and control populations, for example through voxel-based analysis techniques.